The Analysis of Outsourcing Service Strategy: Case Study at PT. Oki Benjaya Persada - Riventa, Yashi Nicafisa (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study uses a qualitative method with a descriptive approach, which involves describing and analyzing the identified issues. In qualitative research, primary and secondary data form the foundation of the study. Primary data in this research were collected through interviews, observation, and documentation, while secondary data were gathered from articles, books, and previous research relevant to the study. The researcher also collected data through questionnaires filled out by 15 participants, employees of PT. Oki Benjaya Persada, as the sample. Choosing a strategy requires a process to ensure that the strategy implemented is appropriate, as the application of strategies today is closely tied to the business world. Outsourcing refers to the use of labor from a service provider to perform tasks for another company. In management, outsourcing means delegating the daily operations and management of a business process to an external party. The purpose of this study is to understand the outsourcing service strategy employed by PT. Oki Benjaya Persada, including service procedures and how the company improves its service strategies to clients. The results of this study show that most employees agree that PT. Oki Benjaya Persada has implemented service strategies in accordance with the established procedures, and clients are satisfied with the services provided. However, the company has not fully implemented solutions to enhance its service strategies, as evidenced by the employees' limited ability to perform tasks that address existing issues.